9(m+2)=9m+18

Simple and best practice solution for 9(m+2)=9m+18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(m+2)=9m+18 equation:


Simplifying
9(m + 2) = 9m + 18

Reorder the terms:
9(2 + m) = 9m + 18
(2 * 9 + m * 9) = 9m + 18
(18 + 9m) = 9m + 18

Reorder the terms:
18 + 9m = 18 + 9m

Add '-18' to each side of the equation.
18 + -18 + 9m = 18 + -18 + 9m

Combine like terms: 18 + -18 = 0
0 + 9m = 18 + -18 + 9m
9m = 18 + -18 + 9m

Combine like terms: 18 + -18 = 0
9m = 0 + 9m
9m = 9m

Add '-9m' to each side of the equation.
9m + -9m = 9m + -9m

Combine like terms: 9m + -9m = 0
0 = 9m + -9m

Combine like terms: 9m + -9m = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 4r^2+11r+6=0 | | -5x+4=-40 | | 1.07/x=15/100 | | D=x(f-d) | | f(x)=cos^5x | | tanx=0.2 | | 5-[-2]= | | x^4-6x^3-9x^2-54x-162=0 | | 5(x-8)=-42+5x | | 3y^2+3y+6=0 | | 2(n-8)-n=n-16 | | 7b^2+29b-30=0 | | -112=-27-5x | | -4(6a-2)= | | 90(x+24)+90(x)=4x(x+4) | | 14.5y=6 | | 21nx-3=0 | | 7a+2=5a+3 | | 7x-10=3(x-2)+5(x-1) | | 95=-47-4(t+6) | | -2x+9y=-6 | | 10-6x-9x+3= | | 8(2c+2)= | | 27(x-1)=3(2x) | | 8y+56=15y | | 20-2v=3v | | 90(x+4)+15(x)=4x(x+4) | | 30+x=7x | | 3y=-15x+270 | | -38+8x=2(8x+1)+8 | | t=0.25(i-32720)+4867.5 | | 4x^2-89x-360=0 |

Equations solver categories